Berpikir Reflektif Siswa dalam Pemecahan Masalah Open Ended Materi Segitiga Berbantuan GeoGebra - Maharani, Elyzabeta Marya; Rosyidi, Abdul Haris (MATHEdunesa, 2024)
Reflective thinking and Geogebra can facilitate students in developing problem solving. Reflective thinking plays a role in formulating problem-solving strategies, while Geogebra functions as an exploratory tool. One of the materials related to reflective thinking and geogebra is triangles. This research is a qualitative descriptive study that aims to describe students' reflective thinking in solving open ended problems with Geogebra-assisted triangle material. Data collection was carried out using tests, interviews, and documentation. The research subjects were 3 class VII students of Public Middle School in Jombang for the 2022/2023 school year who got solutions in the form of acute triangles, right triangles, and obtuse triangles. Data were analyzed using the stages of reflective thinking in problem solving adapted by Dewey. The results showed that when they first read the problem, students felt confused, depressed, relieved, and normal. Students remember similar problems in terms of both context and form. Students identify information on the problem by reading the problem carefully or considering known and unknown information. Students connect what is known and asked using the flat shape concept they have. Students state that the information provided on the problem is sufficient or insufficient based on the calculation of the height of the triangle. When students remember problems with similar contexts, they will use that knowledge to solve current problems. Students find the concept of triangles and Geogebra exploration that can be used in solving problems. Alternative student strategies in solving problems related to the formula for determining the height of a triangle, problem solving steps, and geogebraic exploration. Students try every alternative strategy they find to determine the most effective strategy. Students reveal that Geogebra helps in drawing triangles. Students express confidence in the solutions given along with the reasons.